In vivo study of follicular statistics in Red Chittagong Cattle of Bangladesh - Deb, GK; Kabir, MA; Miraz, MFH; Hossain, SMJ; Afroz, MF; Nahar, TN; Mostofa, MK (Bangladesh Journal of Animal Science, 2018)
The objective of this research was to generate baseline information on follicular statistics of Red Chittagong Cattle (RCC).Ten heifers and ten regular breeder RCC cows were selected randomly from BLRI Research Herd. The ovary was grasped by inserting left hand through the rectum and the follicles were visualized by inserting a sectorial probe through the vagina. Ovarian follicles were visualized and recorded by counting on the screen of ultrasonography machine. All visible follicles (>2.0mm) were counted and graded as small (<3.0mm), medium (3.0 to 8.0mm) and large (>8.0mm). The follicles were measured 3 times at a 3-day interval period without considering the stage of the reproductive cycle of the experimental animals. During this experiment, a total of 137 follicles (66 in Heifers and 71in cows) were observed from 10 heifers and 10 cows. The corpus luteum was observed either in the left or right ovary of 25.0% heifers and 35.0% cows. In heifer, 40.91, 45.45 and 13.64% of the observed follicles were belonged to small, medium and large groups, respectively. The percentage of small, medium and large follicles in the cow ovaries were 54.93, 39.44 and 5.63% accordingly. The number of follicles in an ovary did not vary (P>0.05) between right and left ovary of a heifer or cow. The diameter of the largest follicle on the ovary was smaller (P<0.05) in heifer (9.43±0.34mm) compared to cow (11.2 ± 0.73mm). This information will be helpful during aspiration of ovarian follicle from donor cows. Bang. J. Anim. Sci. 2018. 47 (1): 47-50